Correlation between expressiveness and syntactic independence of Russian onomatopoeic verbal interjections - Oksana Kanerva (Poljarnyj Vestnik: Norwegian Journal of Slavic Studies, 2018)
This article considers Russian onomatopoeic verbal interjections due to the fact that these linguistic units possess a unique grammatical feature of being either completely syntactically independent or act as members of sentence, depending on the context and speaker’s communicative intention. Moreover, there is ambiguity concerning their expressiveness. In some cases they are prosodically foregrounded and have reduplicated morphemes, in others no pauses in speech separate them from the host construction and no expressive morphology is demonstrated. This research aims at establishing correlation between prosodic/morphological expressiveness and syntactic independence of Russian onomatopoeic verbal interjections with the help of a statistical model. Firstly, corpus analysis of data from the Russian Corpus of Spoken Language is applied examine expressiveness of these linguistic units, as well as to investigate their syntactic independence. Finally, a Log-Linear Statistical Model is applied to establish dependencies between absence/presence of these three features and to determine which ones of them have significant correlations.